Venom complexity of Bothrops atrox (common lancehead) siblings - Hatakeyama,Daniela Miki (2020)
Abstract Background: Variability in snake venoms is a well-studied phenomenon. However, sex-based variation of Bothrops atrox snake venom using siblings is poorly investigated. Bothrops atrox is responsible for the majority of snakebite accidents in the Brazilian Amazon region. Differences in the venom composition of Bothrops genus have been linked to several factors such as ontogeny, geographical distribution, prey preferences and sex. Thus, in the current study, venom samples of Bothrops atrox male and female siblings were analyzed in order to compare their biochemical and biological characteristics. Methods: Venoms were collected from five females and four males born from a snake captured from the wild in São Bento (Maranhão, Brazil), and kept in the Laboratory of Herpetology of Butantan Intitute. The venoms were analyzed individually and as a pool of each gender. The assays consisted in protein quantification, 1-DE, mass spectrometry, proteolytic, phospholipase A2, L-amino acid oxidase activities, minimum coagulant dose upon plasma, minimum hemorrhagic dose and lethal dose 50%. Results: Electrophoretic profiles of male’s and female’s venom pools were quite similar, with minor sex-based variation. Male venom showed higher LAAO, PLA2 and hemorrhagic activities, while female venom showed higher coagulant activity. On the other hand, the proteolytic activities did not show statistical differences between pools, although some individual variations were observed. Meanwhile, proteomic profile revealed 112 different protein compounds; of which 105 were common proteins of female’s and male’s venom pools and seven were unique to females. Despite individual variations, lethality of both pools showed similar values. Conclusion: Although differences between female and male venoms were observed, our results show that individual variations are significant even between siblings, highlighting that biological activities of venoms and its composition are influenced by other factors beyond gender.